Perioperative endoscopy of the whole small bowel in Crohn's disease. Issue 5 (May 1993) - Lescut, D; Vanco, D; Bonnière, P; Lecomte-Houcke, M; Quandalle, P; Wurtz, A; Colombel, J F; Delmotte, J S; Paris, J C; Cortot, A
Abstract : The aim of this study was to search for small bowel lesions by means of a perioperative endoscopy in 20 patients operated on for Crohn's disease. Seven women and 13 men (mean age 29 years) had a total retrograde exploration to the angle of Treitz during an ileocolectomy (16 of 20 patients) or a colonic or ileal resection (four of 20 patients). Endoscopic exploration was completed, through an enterotomy, from the surgical area to the angle of Treitz. Periendoscopic biopsy samples were taken on macroscopic lesions and every 20 cm systematically. In 13 of 20 cases, various lesions scattered over the whole small intestine were found. These were aphthoid ulcerations (10 patients), superficial ulcerations (seven patients), mucosal oedema (three patients), non-ulcerative stenosis (three patients), erythema (two patients), pseudopolyps (two patients), deep ulcerations (two patients), and ulcerative stenosis (one patient). In seven patients none of the lesions detected at perioperative endoscopy had been recognised by preoperative evaluation or surgical inspection of the serosal surface. A typical granuloma was found at biopsy of lesions identified by endoscopy in three cases and at biopsy of an apparently healthy area in one case. Thus 65% of patients operated on for Crohn's disease had lesions of the small intestine detected by endoscopy, which were unrecognised before surgery in more than half of the cases.